3D Printed Multilayer Graphite@SiO Structural Anode for High‐Loading Lithium‐Ion Battery. Issue 3 (5th January 2022) - He, Wenjie; Chen, Chenglong; Jiang, Jiangmin; Chen, Zhijie; Liao, Haojie; Dou, Hui; Zhang, Xiaogang
Abstract: To satisfy the increasing demand for higher energy density, the fabrication and structural designs of three‐dimensional (3D) thick electrodes have received considerable attention. In this work, cheap commercial graphite (Gt) and silicon monoxide (SiO) were chosen as raw materials. We have took advantage of the multi‐layer biscuit structure feature to the 3D Gt@GS (Gt@Gt/SiO) electrode with high loading through a modified 3D printing technology. Such a unique structure can not only effectively accommodate the volume expansion in all directions, but also provide a 3D transport channel to enhance the mobility of electrons and ions in the thick electrodes. The obtained 3D Gt@GS electrode, as a freestanding material, shows high capacity and good cycling stability. Especially, the 3D Gt@GS electrode after 120 cycles has achieved a reversible capacity of 3.52 mAh cm −2 at 3.6 mA cm −2 . In addition, we have successfully fabricated a 3D plane‐shaped batteries via a direct ink writing technology and a fused deposition technology. The heterotypic battery assembled can be utilized as an external power supply for the aircraft model. This work demonstrates that the structural battery combined with structural load and 3D printing technology is versatile enough to meet the demand of energy storage systems for high energy density. Abstract : Printing electrodes : Here, we have taken advantage of the multi‐layer biscuit structure feature to the 3D Gt@GS electrode with high loading. It achieves a reversible capacity of 3.52 mAh cm −2 at 3.6 mA cm −2 after 120 cycles. In addition, we have successfully fabricated a 3D plane‐shaped battery via a direct ink writing technology and a fused deposition technology, which can be utilized as an external power supply for the aircraft model.